Black Victorians hidden in history - Abraham, Keshia Nicole; Woolf, John Elgin 1908-1980 (Duckworth, 2022)
'Black Victorians' shows how Black lives were visible, present and influential - not temporary presences but established and rooted; and how paradox and ambivalence characterised the Victorian view of race